Improving Learning Processes and Outcomes Through the Problem Based Learning Model in Natural Science Learning in Class IV SDN 127/II Sungai Arang - Sri rahayu; Subhanadri; Elvima Nofrianni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This study was conducted in the form of action research carried out in the classroom with a Descriptive and numerical in nature approach, participants studied of this research are 15 students of grade IV SDN 127/II Sungai Arang At the implementation stage, this research consists of two cycles carried out by the researcher. Achievements of this From the results of the study it is known that use of problem-based learning strategies models is able to improve the process and results of learning science in class IV SDN 127/II Sungai Arang. This can be seen from the teacher's teaching process in cycle I reaching 84%, in cycle 2 the teacher's teaching process increased by 94%, The improvement in the teacher teaching process fromcycle I to cycle 2 increased by 10%.The learner's education process in cycle achieved 61%, then in the cycle 2 the student studying process boosted by 80%. The rise in the student learning process from cycle I to cycle II increased by 19%, Improving student learning achievement in In the first and second cycle stages with 17%. In addition, An increase also occurred in learning achievement, it is known that in cycle 1 student learning outcomes reached 60% and increased in cycle 2 by 87%, Improving student learning outcomes in cycle 1 to cycle 2 reached 27%. classroom action research using the Problem Based Learning model in learning science has been proven to improve the process and achievement of deep learning class IV on state elementary school127/II Sungai Arang.